Molecular Recognition of the Hybrid‐2 Human Telomeric G‐Quadruplex by Epiberberine: Insights into Conversion of Telomeric G‐Quadruplex Structures. (18th July 2018) - Lin, Clement; Wu, Guanhui; Wang, Kaibo; Onel, Buket; Sakai, Saburo; Shao, Yong; Yang, Danzhou
Abstract: Human telomeres can form DNA G‐quadruplex (G4), an attractive target for anticancer drugs. Human telomeric G4s bear inherent structure polymorphism, challenging for understanding specific recognition by ligands or proteins. Protoberberines are medicinal natural‐products known to stabilize telomeric G4s and inhibit telomerase. Here we report epiberberine (EPI) specifically recognizes the hybrid‐2 telomeric G4 predominant in physiologically relevant K + solution and converts other telomeric G4 forms to hybrid‐2, the first such example reported. Our NMR structure in K + solution shows EPI binding induces extensive rearrangement of the previously disordered 5′‐flanking and loop segments to form an unprecedented four‐layer binding pocket specific to the hybrid‐2 telomeric G4; EPI recruits the (−1) adenine to form a "quasi‐triad" intercalated between the external tetrad and a T:T:A triad, capped by a T:T base pair. Our study provides structural basis for small‐molecule drug design targeting the human telomeric G4.